Rehabilitation for shoulder instability. Issue 5 (6th April 2010) - Jaggi, A; Lambert, S
Abstract : Both structural and non-structural components can contribute to shoulder instability. Classification and therefore management must recognise these factors to achieve functional stability. This paper discusses a classification system proposing three types of shoulder instability recognising the structural and non-structural components and that a continuum exists between pathologies. Structural causes can be addressed with surgical intervention, but non-structural causes such as altered neuromuscular control within the rotator cuff should be addressed conservatively. The purpose of this article is to describe the types of instability and guide appropriate management, helping to avoid surgery in inappropriate cases and ensure that effective rehabilitation has been achieved.